General and sex profile of women with partner affected by premature ejaculation: results of a large observational, non‐interventional, cross‐sectional, epidemiological study (IPER‐F). (17th August 2018) - Verze, P.; Arcaniolo, D.; Imbimbo, C.; Cai, T.; Venturino, L.; Spirito, L.; Califano, G.; La Rocca, R.; Mirone, V.
Abstract: Background: Couple distress is a crucial point in premature ejaculation (PE). PE has been associated with significant bother, interpersonal problems, and dissatisfaction with sexual intercourse for both men and their partners. Objectives: The primary objective of this study was to assess the effect of PE on female sexuality in female partners of men affected from PE. Secondary objectives were to assess the impact of PE on female sexual quality of life, to assess the presence of sexual problems of the male partner, and to evaluate the prevalence and characteristics of comorbidities. Materials and methods: Adult women aged 18 to 80 years old, sexually active, were randomly sampled from the patient lists of General Practitioners in Italy and were included in this observational, non‐interventional, cross‐sectional epidemiological study. Subjects were asked to fill: a general questionnaire regarding anthropometric data, lifestyle, marital status, education, occupation, economic conditions, general health status, comorbidities, and sexual habits; the Sexual Quality of Life Questionnaire‐Female (SQoL‐F); the Female Sexual Distress Scale (FSDS‐R‐PE); the Self‐rating Depression Scale (SDS); and Self‐rating Anxiety Scale (SAS). In addition, females reported about their partner's ejaculation time and the presence of sexual dysfunctions. Results: A total of 3, 104 women were included. Mean age was 45.1 years. Woman with PE partners presented a higher percentage of sexual dysfunction and reported more anxiety compared with female partners of men not affected from PE (42.69% vs. 20.56% and 30.95% vs. 15, 34%, respectively). In addition, they referred more sexual dysfunction in their partners. Hypertension, hypercholesterolemia, arthritis, heart diseases, thyroid disease, a history of menopause, or hysterectomy resulted in significantly more prevalence in women with PE partners. Discussion and conclusions: Female partners of PE patients present an increased prevalence of sexual distress, a reduced quality of sexual life, and an increased anxiety score when compared to women whose partners are not affected from PE.